TRAINING, ENVIRONMENT, AND EMPLOYEE PERFORMANCE : SYSTEMATIC LITERATURE REVIEW - Rosa Indah Parawansah; Sopiah Sopiah; Syihabudhin Syihabudhin (Universitas Nusa Cendana, 2025)
This article aims to analyze training, work environment, and employee performance. This article was prepared using the Systematic Literature Review (SLR) method. SLR is a systematic literature review method that identifies, reviews, evaluates, and interprets all available research. With this method, researchers review and identify journals in a structure that, in each process, follows predetermined steps. Employee performance is one of the main factors for the company to achieve its goals. Apart from being a factor in achieving goals, employee performance is also a way to measure the quality of human resources in a company. The analysis of various journals indicates that both training and the work environment significantly influence employee performance. The training given to employees will improve their performance, and a comfortable work environment will also improve employee performance. Keywords: Training; Environment; Employee Performance